(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This text evolves like a dance, like a dramaturgy of possible gestures to choreograph the present in its complexities and mobility. This dramaturgical construction makes it possible to imagine a choreography based on the notions of enchantment and refuge, as (im)possible practices for thinking about the role of artists and creators in the face of the climate crisis. It is worth recollecting that dramaturgy, in this case, is not understood as a manual or musical score, but rather as an open field to open lines of flight from a problem where words are no longer enough. These words want to be spread out and arouse a desire for movement. It is necessary to imagine, to fable, to speculate, and speculation requires a body. It is an earthly relationship. It demands that we play and play in another plan of change. Choreographing, pausing, landing, rolling, dancing, moving protagonists and sharing, are some clues to get started.